Liposomal carrier systems for encapsulation of drugs using bicellar mixtures - Lee, Bao Jun (Nanyang Technological University, 2024)
Drug delivery systems can be in the form of particles in which the drug is protected by a core material that is biocompatible with the body. Encapsulation of drugs in liposomes holds great potential for enhancing drug stability and targeted drug delivery. However, there are limitations to liposomes including physicochemical instability and poor encapsulation efficiency. As such, the use of bicelles holds greater potential over conventional liposomes in terms of stability and drug encapsulation efficiency. The drugs used in this research are vitamin B1 (hydrophilic) and idebenone (hydrophobic). Through the usage of bicellar mixture which includes long-chain molecules like DOPC and cholesterol, combined with short-chain molecules like lauric acid. This research aims to evaluate the physicochemical properties of bicelles, such as particle size, distribution, and encapsulation efficiency of drugs. The bicelles will be fabricated using the LUCA cycles (freeze-thaw-vortex cycles) by varying the q-ratio (0, 2, 5, 8, 10, and 20) and total lipid concentration (2mM, 5mM and 10mM). Characterisation of particle size, polydispersity index (PDI) and stability of all bicelles will be performed via Dynamic Light Scattering (DLS), while characterisation of encapsulation efficiency will be performed via UV/Vis. The results confirm that bicelles are smaller with a lower q-ratio. Vitamin B1 bicelles are larger while idebenone bicelles are smaller at higher total lipid concentration. Furthermore, vitamin B1 bicelles can achieve higher encapsulation efficiency of 73.3% than conventional liposomes and idebenone bicelles can achieve 100% encapsulation efficiency. Both vitamin B1 and idebenone shows good stability of encapsulation efficiency, enabling them to be encapsulated for up to a month without any significant efficiency loss. The sample with the best stability would be vitamin B1 bicelles at 2mM with q-ratio = 2 having the smallest average size of 226.9 nm, and the lowest PDI of 0.273. Overall, the stability of particle size and PDI for vitamin B1 bicelles are much better than idebenone bicelles. Further work is needed to investigate the stability of idebenone and may incorporate other external environmental factors including temperature and pH.